Queueing systems with renovation. (1997) - Kreinin, A. Ya.
Abstract : We study in this paper-single channel queueing systems with renovation. Such models are often encountered in computer science applications. Explicit solutions are discussed for the queues with Poisson input flow and for queues with general input and exponential service times.